A novel nyavirus lacking matrix and glycoprotein genes from Argas japonicus ticks - Kobayashi, Daisuke; Komatsu, Noriyuki; Faizah, Astri Nur; Amoa-Bosompem, Michael; Sawabe, Kyoko; Isawa, Haruhiko (Virus research, 2021)
•A new nyavirus, designated Sekira virus (SEKRV), was detected from Argas japonicus ticks in Japan.•SEKRV lacks the genes encoding matrix protein (M) and glycoprotein (G).•This is the first report of a nyavirus deficient in M and G genes in nature. Viruses are highly diverse and are the sole agents that can infect organisms in all domains of life. Viruses are defined as capsid-encoding organisms as opposed to ribosome-encoding cellular organisms. However, recent advances in virology indicate the existence of unique viruses that do not meet this basic definition, such as capsidless viruses. During virome analysis of the soft tick Argas japonicus, we identified virus-like sequences closely related to the members of genus Nyavirus (family Nyamiviridae). Further analysis revealed sequences derived from a novel nyavirus that lacks two structural protein genes, matrix (M) and glycoprotein (G). This unique nyavirus is tentatively named Sekira virus (SEKRV). To our knowledge, this is the first study to report a nyavirus deficient in M and G genes in nature. The mechanism of infection, replication, and persistence of SEKRV remain unknown, yet this finding provides new insight into virus evolution and the diverse way of viral life in nature.